Long-term results of arthroscopic and mini-open repair of small- to medium-size full-thickness rotator cuff tears. (May 2019) - van Deurzen, DFP; Scholtes, VAB; Willems, WJ; Geerdink, HH; van der Woude, HJ; van der Hulst, VPM; van den Bekerom, MPJ
Background: This retrospective cohort study evaluated functional outcome and structural integrity after arthroscopic- or mini-open repair of small- to medium-size rotator cuff tears assessed at long-term follow-up. Methods: All patients operated between 2001 and 2004 were invited to participate. Functional outcome was measured by Constant–Murley Score, Disability of Arm, Shoulder and Hand and Oxford Shoulder Score. Quality of life was assessed with EuroQol Health 5 Dimension. Patient satisfaction was assessed in terms of pain and overall result. Structural integrity of the rotator cuff repair was determined using ultrasound. Results: Of the eligible 62 patients, 44 patients were available for follow-up. After a mean of 11.3 years, 76% of the patients had good to excellent functional outcome on the Constant–Murley Score (median 82, range 29–95). The majority of patients reported good results on both Disability of Arm, Shoulder and Hand and Oxford Shoulder Score (median Disability of Arm, Shoulder and Hand 5.0, range 1.0–54; median Oxford Shoulder Score 19, range 13–39). The quality of life was also good (mean EuroQol Health 5 Dimension utility score 0.88, standard deviation 0.12). Eighty per cent was satisfied with the overall result. Ultrasound examination revealed structural integrity in 76% of all cases. Conclusion: This study shows that functional outcome is good and structural integrity is high for the majority of patients 11.3 years after repair of small- to medium-size rotator cuff lesions.